Urban form and vacant shops: can one explain the other? A case study in Portugal - Saraiva, Miguel Marinho (2018)
Shopping is much more than a wealth-generator in post-modern so- cieties; it is intrinsically linked with the way people experience the city and an indivisible part of their day-to-day social experiences. Consequently, the literature has gradually recognized that commercial geographies are not just a consequence of economic market logics. It has been proven that there is a relationship between store-types and urban morphology, and that commerce is an important catalyst for urban regeneration and revitalization. Thus, the ur- ban form can also be a cause for the lack of success of a shop. The amount of vacant shops has been signaled as an important problem in urban areas, affec- vkpi"vjg"uvtwevwtg"cpf"vjg"kfgpvkv{"qh"pgkijdqwtjqqfu."cpf"tgÞgevu"vjg"pgicvkxg" effects of the economic-crisis. Strategies to overcome this problem are usual- ly economically-oriented and fail to capitalize on the new-found relationships between store-success and urban morphology. Thus this research wishes to test yjgvjgt"vjgtg"ctg"kpfggf"eqttgncvkqpu"dgvyggp"urgekÝe"oqtrjqnqikecn"hgcvwtgu" and the existence of vacant shops, and consequently to discuss how changes in the urban environment can contribute to overcome, and even prevent, such cases. The geographical distribution of vacant shops in a sample of Portuguese cities was set against morphological variables such as building age or centra- lity in the network. Positive association was found, for example, between new developments and vacant shops, questioning the need for more store space in certain areas; and, particularly outside central neighborhoods, between open shops and high travel-through (rather than highly central) segments.